2010
DOI: 10.1038/jcbfm.2010.105
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Modeling in Primate Cortex

Abstract: We report new results on blood flow modeling over large volumes of cortical gray matter of primate brain. We propose a network method for computing the blood flow, which handles realistic boundary conditions, complex vessel shapes, and complex nonlinear blood rheology. From a detailed comparison of the available models for the blood flow rheology and the phase separation effect, we are able to derive important new results on the impact of network structure on blood pressure, hematocrit, and flow distributions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 37 publications
5
90
1
Order By: Relevance
“…On the contrary, when rescaling the perfusion flux Q by the voxel surface S, its evaluation at different scales does not statistically differ anymore (Student's t-tests P40.75 in Figure 2C). Albeit presented here for one in vivo blood rheology model, 11 this finding is robust to any rheology models previously analyzed 10 so that this observation is a very strong property of blood perfusion spatial distribution. We also statistically tested the Q/V 1/6 normalization 6 and found that it does not provide a scale-invariant quantity for the four different voxel sizes chosen.…”
Section: Synchrotron Microtomographymentioning
confidence: 82%
See 3 more Smart Citations
“…On the contrary, when rescaling the perfusion flux Q by the voxel surface S, its evaluation at different scales does not statistically differ anymore (Student's t-tests P40.75 in Figure 2C). Albeit presented here for one in vivo blood rheology model, 11 this finding is robust to any rheology models previously analyzed 10 so that this observation is a very strong property of blood perfusion spatial distribution. We also statistically tested the Q/V 1/6 normalization 6 and found that it does not provide a scale-invariant quantity for the four different voxel sizes chosen.…”
Section: Synchrotron Microtomographymentioning
confidence: 82%
“…Figure 1A illustrates the largest cube of 8 mm 3 that could be extracted from the complete reconstruction of a cylindrical sample of primate cortex excluding the pia matter ( Figure 1B), which is essential for applying relevant boundary conditions. 10 The resulting prediction for the blood pressure and flow distribution depends on the considered blood rheological model; we already analyzed this issue in a recent study. 10 Here, we show that the CBF measurement depends on the size of the processed virtual voxel, i.e., the size of the cubic box.…”
Section: Synchrotron Microtomographymentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 The conventional method of medical imagery is to analyze the tissues (after special pretreatment) with the use of optical-or electron microscope depending on the object of examination. Traditional microscopic methods cannot detect overlapping structures which are small relative to the thickness of the tissue.…”
Section: Introductionmentioning
confidence: 99%